Analysis Of Travel Business Competitive Strategy (Case Study In PT. Jasa Tour And Travel Medan) - Sonia Benedicta Simanjuntak (IHSA Institute, 2022)
Business competition is a common thing in the corporate world. As time goes by, business competition faced by the company is also getting tougher. This requires the company to be more careful in formulating a strategy to win the competition. Seeing the fierce increasing competition, the authors observed that PT. JAS Tour and Travel needs to establish the exact formulation of competitive strategy to find the factors of internal and external key that can affect the level of success of the strategy. Strength of business travel agencies will be capital in competitive advantage of opportunities that exist.This study aims to determine competitive strategy what is the most appropriate for use by PT. JAS Tour And Travel in order to maintain the existence amid increasing fierce competition. The strategy formulated by analyzing the internal and external forces, and the opportunities and threats of the company.The method used is a qualitative descriptive study to identify the strengths, weaknesses, opportunities and threats. Analysis of the data used is the data collection phase, the stage of data analysis and decision-making stage.Based on research conducted by SWOT analysis as a media strategy formulation, PT. JAS Tour And Travel supports aggressive strategy. The input stage includes EFE matrix with a total value of 2.85 and IFE matrix with a total value of 2.90. While the results of the matrix CP is known that the indicators of competition are: PT. JAS Tour And Travel 3.85, Senandika Tour And Travel amounted to 3.60, and Manalu Jaya Travel at 3.65. SWOT matrix matching phase and the matrix IE. SWOT analysis showed that PT. JAS Tour And Travel is in quadrant I, which states that PT. JAS Tour And Travel supports aggressive strategy. From the matrix IE, known that. JAS Tour And Travel is in quadrant V which is a strategy to preserve and defend. Therefore, PT. JAS Tour And Travel can consider two alternative strategies, namely market penetration and product development. Phase decision to use a QSPM matrix and obtained a total value of the highest appeal and the right to apply the company is a market penetration strategy with a value of 6.00. The proposed strategy can be applied to improve the quality of services and conduct market development.